Educators' Emotions in Mainstream Settings/How Do Teachers Feel When Facing Difficulties and Challenging Behaviours from Students with SEND? - Koumpou Vasiliki; Triantafyllaki Angeliki (2017)
Aims and Purpose of the Study, Literature Review, Introduction to the Chapter, The Role of the Teacher in Special Educational Needs, Emotions, Support, Methodology, Data Collection Tools, Pilot Study, Research Design, Data Analysis, Findings, Manja, Mirella, Daisy, Petra, Chara, Ismene, Discussion, Emotional Exhaustion, Relating to Students, Ideas and Needs for Support, Conclusion, References, Appendices.